Literasi Media Melalui Video Podcast pada Kalangan Mahasiswa Yogyakarta: (Studi pada Mahasiswa Ilmu Komunikasi Universitas Ahmad Dahlan, Universitas Amikom Yogyakarta, dan Universias Mercu Buana Yogyakarta) - Annisa Ishlahtus Shohwah; Arif Ardy Wibowo (Jurnal Penelitian Pers dan Komunikasi Pembangunan, 2021)
Video podcasts become one of the digital content included in a combination format, combined writing, video, and audio packed so that it becomes content distributed in digital format. The ease of accessibility of podcast video content makes it important to apply media literacy to remain critical of the message's various meanings in the content in the video podcast. This study aims to determine the level of media literacy through video podcasts among students of Communication Sciences Yogyakarta. The method used in this study is a descriptive quantitative method with the concept of measuring individual competence framework media literacy. Samples from this study were active students of Communication Sciences in 2019/2020 at Ahmad Dahlan University, Mercu Buana University Yogyakarta, and AMIKOM University Yogyakarta, with a total sample of 368 respondents. This study showed that the level of media literacy through video podcasts among students of Communication Science Yogyakarta is at a high level (advanced) with details of technical skills are in the advanced category of 80%, critical understanding ability at the advanced level of 86%. Communicative abilities are at the medium level of 59%. This shows that Yogyakarta communication students can use very high media, analyze excellent information, and participate and communicate actively through social media.